A cellularized biphasic implant based on a bioactive silk fibroin promotes integration and tissue organization during osteochondral defect repair in a porcine model - Pérez Silos, Vanessa; Moncada Saucedo, Nidia Karina; Peña Martínez, Víctor Manuel; Lara Arias, Jorge; Marino Martínez, Iván Alberto; Camacho Morales, Alberto; Romero Díaz, Víktor J.; Lara Banda, María del Refugio; García Ruíz, Alejandro; Soto Domínguez, Adolfo; Rodríguez Rocha, Humberto; López Serna, Norberto; et al. (Molecular Diversity Preservation International, 2019)
In cartilage tissue engineering, biphasic scaffolds (BSs) have been designed not only to influence the recapitulation of the osteochondral architecture but also to take advantage of the healing ability of bone, promoting the implant’s integration with the surrounding tissue and then bone restoration and cartilage regeneration. This study reports the development and characterization of a BS based on the assembly of a cartilage phase constituted by fibroin biofunctionalyzed with a bovine cartilage matrix, cellularized with differentiated autologous pre-chondrocytes and well attached to a bone phase (decellularized bovine bone) to promote cartilage regeneration in a model of joint damage in pigs. BSs were assembled by fibroin crystallization with methanol, and the mechanical features and histological architectures were evaluated. The scaffolds were cellularized and matured for 12 days, then implanted into an osteochondral defect in a porcine model (n = 4). Three treatments were applied per knee: Group I, monophasic cellular scaffold (single chondral phase); group II (BS), cellularized only in the chondral phase; and in order to study the influence of the cellularization of the bone phase, Group III was cellularized in chondral phases and a bone phase, with autologous osteoblasts being included. After 8 weeks of surgery, the integration and regeneration tissues were analyzed via a histology and immunohistochemistry evaluation. The mechanical assessment showed that the acellular BSs reached a Young’s modulus of 805.01 kPa, similar to native cartilage. In vitro biological studies revealed the chondroinductive ability of the BSs, evidenced by an increase in sulfated glycosaminoglycans and type II collagen, both secreted by the chondrocytes cultured on the scaffold during 28 days. No evidence of adverse or inflammatory reactions was observed in the in vivo trial; however, in Group I, the defects were not reconstructed. In Groups II and III, a good integration of the implant with the surrounding tissue was observed. Defects in group II were fulfilled via hyaline cartilage and normal bone. Group III defects showed fibrous repair tissue. In conclusion, our findings demonstrated the efficacy of a biphasic and bioactive scaffold based on silk fibroin and cellularized only in the chondral phase, which entwined chondroinductive features and a biomechanical capability with an appropriate integration with the surrounding tissue, representing a promising alternative for osteochondral tissue-engineering applications.